2020
DOI: 10.1038/s41598-020-78367-2
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and molecular characterization of multidrug-resistant Escherichia coli from chicken meat

Abstract: Antibiotic-resistant Escherichia coli (E. coli) are common in retail poultry products. In this study, we aimed to isolate and characterize multidrug resistant (MDR) E. coli in raw chicken meat samples collected from poultry shops in Sylhet division, Bangladesh, as well as to determine correlation between resistance phenotype and genotype. A total of 600 chicken meat swabs (divided equally between broiler and layer farms, n = 300 each) were collected and the isolates identified as E. coli (n = 381) were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 58 publications
9
48
3
Order By: Relevance
“…Factors such as environmental conditions, geographical locations, and mixed infection of samples with other microbes have been suggested to affect prevalence of bacteria including E. coli [30] and this could be the causes of the differences in prevalence. *MAR isolates are those with resistance to at least two antibiotics [24] From this study, E. coli isolates were more resistant to streptomycin, sulphamethoxazole /trimethoprim, and ampicillin, which is similar to studies by [27], [31], and [32], but less resistant to imipenem, cefotaxime and ceftazidime. This finding is similar to a study by [33].The observed resistance of the E. coli from this study to commonly used antibiotics is not extraordinary as many studies worldwide have reported it [34,35] .…”
Section: Molecular Detection Of Extended-spectrum Beta-lactamase Genessupporting
confidence: 75%
“…Factors such as environmental conditions, geographical locations, and mixed infection of samples with other microbes have been suggested to affect prevalence of bacteria including E. coli [30] and this could be the causes of the differences in prevalence. *MAR isolates are those with resistance to at least two antibiotics [24] From this study, E. coli isolates were more resistant to streptomycin, sulphamethoxazole /trimethoprim, and ampicillin, which is similar to studies by [27], [31], and [32], but less resistant to imipenem, cefotaxime and ceftazidime. This finding is similar to a study by [33].The observed resistance of the E. coli from this study to commonly used antibiotics is not extraordinary as many studies worldwide have reported it [34,35] .…”
Section: Molecular Detection Of Extended-spectrum Beta-lactamase Genessupporting
confidence: 75%
“…Although one of our study limitation is the inability to provide an evidence of a link between the presence of plasmids and the antimicrobial resistance profiles observed. Antibiotic resistant genes encoding multiple resistance to antibiotic classes such as fluoroquinolones, aminoglycosides and beta-lactams borne on plasmids are capable of bacteria to bacteria transmission via horizontal gene transfer among bacterial communities [22,23] Interestingly, carriage of plasmids among the selected isolates was more frequent in bacteria isolated from chicken indicating chicken meat may be a reservoir of antimicrobial resistance as previously opined elsewhere [24].…”
Section: Discussionmentioning
confidence: 64%
“…Antibiotic use in veterinary medicine is thought to increase the risk of antibiotic-resistant bacteria that can be transmitted to humans [ 36 ]. High prevalence rates of Escherichia coli with ESBL-mediated resistance to third-generation cephalosporins and MCR-1-mediated colistin resistance have been reported from livestock and food in recent years [ 37 , 38 , 39 ]. As expected, the resistance to ampicillin was frequent among the study collection due to the presence of intrinsic beta-lactamase genes in Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%